2001
DOI: 10.1177/096739110100900407
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy Based Thermal Stabilizer for Poly(Vinylchloride)

Abstract: A tetrafunctional epoxy resin was prepared and characterized by epoxy equivalent weight, percentage nitrogen, IR spectroscopy and number average molecular weight (Mn) determined by GPC. The resin was evaluated as a thermal stabilizer for polyvinylchloride (PVC). The stabilizing efficiency was tested by yellowness index, HCl liberation, UV absorption, induction time, and changes in mechanical properties (tensile strength, elongation at break and Shore-A hardness). Epoxy resins with several epoxy groups are effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…With the inclusion of epoxy groups, this plasticizer should also have the added advantage of being a heat stabilizer. Previous studies have shown that epoxides are effective PVC thermal stabilizers [17]. The use of ECTO not only has the potential to reduce the production of DEHP but may also minimize the manufacture of heat stabilizers, chemicals that are often hazardous to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…With the inclusion of epoxy groups, this plasticizer should also have the added advantage of being a heat stabilizer. Previous studies have shown that epoxides are effective PVC thermal stabilizers [17]. The use of ECTO not only has the potential to reduce the production of DEHP but may also minimize the manufacture of heat stabilizers, chemicals that are often hazardous to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the behavior of the PVC tubes exposed to long periods of solar radiation, and which the property alterations in relation to the tube never exposed, some compared properties had been determined and soon after calculated parameters (δ) that relates the property of the sample in the study to the properties of the standard sample. Tests of traction, compression, bend and impact, in the five samples of the each type studied, were carried out, to analyze the waste levels associated to the thermal and UV degradations and evaluate its causes and effects [1][2][3][4][5][22][23][24][25][26][27][28][29][30][31][32] . The comparative parameters (δ) they are calculated in agreement with the Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Specialized literature shows that the susceptibility to the thermal degradation of PVC reaches a critical level from temperature above 60 °C in its surface. The UV degradation also represents a restriction to the use of solar collectors made of PVC tubes, once radiations with this wavelength affect the mechanical integrity of this kind of material [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…303 Lead-based stabilizers for polyvinyl chloride are mostly banned and only allowed for a few applications.…”
Section: Stabilizers For Polyvinyl Chloridementioning
confidence: 99%